AGRICULTURE 4.0: DIGITAL TRANSFORMATION IN THE PRODUCTION CHAIN FOR EFFICIENCY AND SUSTAINABILITY IN THE AGRO-INDUSTRIAL SECTOR - Pistori, Eric Marcel Lemes; Neto, Mario Mollo (Seven Editora, 2024)
The use of high technology in agro-industrial production is a reality in crops, reinforcing the relevance of Agriculture 4.0 as a transforming agent through digitalization and integration of processes. Digital transformation connects all links in the production chain, allowing real-time data from the field to be disseminated and used to improve the control of operations and support strategic decisions with precision. This advancement facilitates more efficient practices, continuous monitoring, and agile responses to environmental and market variables. In this context, this article presents a Systematic Literature Review, addressing the state of the art of Agriculture 4.0, its technologies and practices applied to the agro-industrial sector. In sequence, a case study is applied with data collection in a company that provides technological solutions aimed at the management of the agro-industrial process of the sugar-energy sector. The objective is to analyze and relate the challenges in the integration between the field, technology and the user of the data, in order to identify critical factors that influence the adherence and success of digital solutions. The research seeks to explore how digitalization can optimize operational efficiency, increase productivity, and create opportunities for knowledge management and sustainability in the agribusiness. It was highlighted in the results that the digital transformation in agribusiness, driven by technology 4.0, is changing the way agricultural activities are managed, bringing significant gains in productivity, sustainability and competitiveness, but the growing presence of technologies 4.0 on farms and organizations indicates the importance of a continuous knowledge management plan, which covers both implementation and after-sales monitoring,  in order to ensure that users have the skills to deal with innovations. This approach allows not only the technological updating of operations, but also the strengthening of human capital, creating a collaborative environment that is adaptable to changes. It was observed that strengthening the practical knowledge base, with a focus on good practices and use models, is essential for Brazilian agribusiness to make the most of the potential of Agriculture 4.0. DOI:https://doi.org/10.56238/sevened2024.037-012